Melicope ptelefolia leaf extracts exhibit antioxidant activity and exert anti-proliferative effect with apoptosis induction on four different cancer cell lines - Mohammad Faujul Kabir; Johari Mohd Ali; Mitra Abolmaesoomi; Onn Haji Hashim (BMC, 2017)
Abstract Background Melicope ptelefolia is a well-known herb in a number of Asian countries. It is often used as vegetable salad and traditional medicine to address various ailments. However, not many studies have been currently done to evaluate the medicinal benefits of M. ptelefolia (MP). The present study reports antioxidant, anti-proliferative, and apoptosis induction activities of MP leaf extracts. Method Young MP leaves were dried, powdered and extracted sequentially using hexane (HX), ethyl acetate (EA), methanol (MeOH) and water (W). Antioxidant activity was evaluated using ferric reducing antioxidant power (FRAP), 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) radicals scavenging and cellular antioxidant activity (CAA) assays. Anti-proliferative activity was evaluated through cell viability assay, using the following four human cancer cell lines: breast (HCC1937, MDA-MB-231), colorectal (HCT116) and liver (HepG2). The anti-proliferative activity was further confirmed through cell cycle and apoptosis assays, including annexin-V/7-aminoactinomycin D staining and measurements of caspase enzymes activation and inhibition. Result Overall, MP-HX extract exhibited the highest antioxidant potential, with IC50 values of 267.73 ± 5.58 and 327.40 ± 3.80 μg/mL for ABTS and DPPH radical-scavenging assays, respectively. MP-HX demonstrated the highest CAA activity in Hs27 cells, with EC50 of 11.30 ± 0.68 μg/mL, while MP-EA showed EC50 value of 37.32 ± 0.68 μg/mL. MP-HX and MP-EA showed promising anti-proliferative activity towards the four cancer cell lines, with IC50 values that were mostly below 100 μg/mL. MP-HX showed the most notable anti-proliferative activity against MDA-MB-231 (IC50 = 57.81 ± 3.49 μg/mL) and HCT116 (IC50 = 58.04 ± 0.96 μg/mL) while MP-EA showed strongest anti-proliferative activity in HCT116 (IC50 = 64.69 ± 0.72 μg/mL). The anticancer potential of MP-HX and MP-EA were also demonstrated by their ability to induce caspase-dependent apoptotic cell death in all of the cancer cell lines tested. Cell cycle analysis suggested that both the MP-HX and MP-EA extracts were able to disrupt the cell cycle in most of the cancer cell lines. Conclusions MP-HX and MP-EA extracts demonstrated notable antioxidant, anti-proliferative, apoptosis induction and cancer cell cycle inhibition activities. These findings reflect the promising potentials of MP to be a source of novel phytochemical(s) with health promoting benefits that are also valuable for nutraceutical industry and cancer therapy.